The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.ecss.2016.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Habitat restoration: Early signs and extent of faunal recovery relative to seagrass recovery

Abstract: The overall intent of restoration is often not only to restore the habitat per se, but to restore the ecosystem services it supplies, and particularly to encourage the return of fauna. Seagrass meadows act as habitat for some of the most diverse and abundant animal life, and as the global loss of seagrass continues, managers have sought to restore lost meadows. We tested how quickly the epifaunal richness, abundances and community composition of experimental restoration plots recovered to that in an adjacent n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 54 publications
(74 reference statements)
2
15
0
Order By: Relevance
“…Seagrass restoration has the lowest success rate, with a median survival of 38% compared with 64.5% for coral reefs (Bayraktarov et al, ). New approaches, involving the use of artificial substratum to facilitate seagrass seedling establishment, have led to recovery (Tanner, ) and their associated biodiversity (McSkimming et al, ). Seagrass damage at smaller scales is reduced or eliminated through modifications to the designs of docks (eliminating the shading impacts of traditional docks) (Gladstone and Courtenay, ) and by replacing traditional boat moorings with seagrass‐friendly moorings (Demers et al, ).…”
Section: Conservation and Management Of Freshwater And Marine Fishesmentioning
confidence: 99%
“…Seagrass restoration has the lowest success rate, with a median survival of 38% compared with 64.5% for coral reefs (Bayraktarov et al, ). New approaches, involving the use of artificial substratum to facilitate seagrass seedling establishment, have led to recovery (Tanner, ) and their associated biodiversity (McSkimming et al, ). Seagrass damage at smaller scales is reduced or eliminated through modifications to the designs of docks (eliminating the shading impacts of traditional docks) (Gladstone and Courtenay, ) and by replacing traditional boat moorings with seagrass‐friendly moorings (Demers et al, ).…”
Section: Conservation and Management Of Freshwater And Marine Fishesmentioning
confidence: 99%
“…Restoration efforts should only be considered in locations where the original stressors resulting in seagrass habitat loss or degradation have been substantially reduced. Seagrass rehabilitation or restoration through seeding (Orth et al, 2006) and transplantation of seedlings (Van Katwijk et al, 2009;McSkimming et al, 2016) are possible options for restoring seagrass habitat however, restocking of seagrass habitats using seedlings or seeds may not be a cost effective or a successful disturbance recovery strategy as life stage survival can depend on many different factors including sediment type, habitat depth, species, seed density and the ability to obtain enough viable seed (Rasheed et al, 2014;Statton et al, 2017). To our knowledge, direct regenerative measures to transplant and restore seagrass and seagrass habitats in PSIDS have occurred only in Kiribati via transplanting (Peter, pers.…”
Section: Seagrass Restoration As An Option For Resilience Buildingmentioning
confidence: 99%
“…Recent reviews of SAV restoration outcomes from Chesapeake Bay and Europe and a global meta-analysis of SAV restoration found that few restored sites survive beyond 1 year (Cunha et al 2012;Luckenbach et al 2011;van Katwijk et al 2016). The results of these reviews contrast with numerous individual studies over the past few decades that have documented examples of successful SAV restoration (Bell et al 2014;Fonseca et al 1996a;Kenworthy et al 1980;McSkimming et al 2016;Sheridan 2004). In some cases, monitoring timeframes much longer than 3 years may be necessary to fully capture the restoration trajectories of SAV beds ( Bell et al 2008McGlathery et al 2012).…”
Section: How Do Restored Coastal Habitats Compare With Natural Habitats?mentioning
confidence: 99%
“…For example, seeding can result in different outcomes from transplanting (Fonseca et al 1990;van Katwijk et al 2016) and the timing of planting, interannual variability in environmental conditions, use of fertilization, and genetics of the donor stock can also influence outcomes (Bologna and Sinnema 2012;Jahnke et al 2015;Kenworthy et al 2018;Orth et al 2009;Powell et al 1991;Reynolds et al 2012). However, nekton and epifauna can respond rapidly to successful SAV restoration, with abundance/density, species composition, and size at restored sites resembling those of natural SAV beds within a couple of years (Fonseca et al 1990(Fonseca et al , 1996bMcSkimming et al 2016;Scapin et al 2016; for exceptions, see Sheridan et al 2003). Colonization by resident epibenthic fauna may be dependent on the restored bed first reaching a minimum shoot density (Fonseca et al 1990(Fonseca et al , 1996b.…”
Section: How Do Restored Coastal Habitats Compare With Natural Habitats?mentioning
confidence: 99%